Crisis Management in the Airline Industry During the COVID-19 Pandemic: A Comparative Analysis of Emirates and Wizz Air - Suchecki, Wiktor (Zarządzanie kryzysowe w branży lotniczej podczas pandemii COVID-19: analiza porównawcza Emirates i Wizz Air, 2025)
The article analyses crisis management in the aviation industry during COVID-19, focusing on differences between airlines with distinct business models. The objective is to identify these differences by comparing the crisis management actions of Emirates and Wizz Air during the pandemic. The article consists of two parts. The first provides a literature review covering crisis management concepts and airline economics, and examines crisis management measures in the air transport sector. The second part defines the methodology and background, mentioning the specifics of COVID-19 pandemic, and briefly presents the characteristics and business models of the carriers – Emirates as a full-service airline and Wizz Air as a low-cost carrier. Next it details the decisions made by both companies and, finally, identifies the differences in their crisis management actions during the pandemic. Emirates adopted a more defensive approach, while Wizz Air pursued aggressive actions.
Quote as: Suchecki, W. (2025). Crisis Management in the Airline Industry During the COVID-19 Pandemic: A Comparative Analysis of Emirates and Wizz Air. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 182-194). Publishing House of Wroclaw University of Economics and Business.
Keywords: crisis; crisis management; air transport; airlines; Emirates; Wizz Air; full-service carrier; low-cost carrier; COVID-19; kryzys; zarządzanie kryzysowe; transport lotniczy; linie lotnicze; przewoźnik tradycyjny; przewoźnik niskokosztowy